Assessing the physical validity of highly-resolved simulation benchmark tests for flows undergoing phase change. (March 2019) - Bardia, Raunak; Trujillo, Mario F.
Highlight: Analysis of the constant interface temperature and incompressible flow treatment in highly-resolved simulation is performed. Abstract: Highly-Resolved Simulation (HRS) studies aimed at solving flows undergoing phase change commonly make the following two assumptions: (i) a constant interface temperature and (ii) an incompressible flow treatment in both the gas and liquid regions, with the exception of the interface. The physical validity of these assumptions is examined in this work by studying a canonical, spherically symmetric bubble growth configuration, which is a popular validation exercise in HRS papers. The reference solutions that are used to examine HRS results are based on a compressible saturated treatment of the bubble contents, coupled to a generalized form of the Rayleigh–Plesset equation, and an Arbitrary-Lagrangian–Eulerian solution of the liquid phase energy equation. Results show that HRS predictions are inaccurate during the initial period of bubble growth, which coincides with the inertial growth stage. Furthermore, this initial period becomes more significant with increasing Jakob number. A closed-form expression for a threshold time, tthreshold, is derived, beyond which the commonly employed HRS assumptions hold. Based on this threshold time, a corresponding bubble radius is obtained, namely 2 β α L t t h r e s h o l d . This radius together with a corresponding Scriven-based temperature profile provide appropriate initial conditions such that HRS treatment based on the aforementioned assumptions remains valid over a broad range of operating conditions.